2022
DOI: 10.4103/jpbs.jpbs_63_22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Utility of Lycopene, Selenium, and Vitamin E in Management of Oral Leukoplakia

Abstract: Objectives: To assess the utility of lycopene, selenium, and vitamin E in the management of leukoplakia. Materials and Methods: In this cross-sectional observational prospective study, 52 patients of oral leukoplakia were divided into 2 groups. Group I patients were prescribed 6 mg of lycopene, 400 I.U. of vitamin E, and 200 μg of selenium twice a day. Group II patients were prescribed a placebo capsule. The clinical improvement was recorded in both groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…One study found that the topical application of vitamin E reduced the lesion size, without any therapeutic effects on the clinical symptoms of OLP. Two of three OL studies found that vitamin E applied orally or topically reduced lesion sizes, and histological changes were also observed [33,34]. One SF study utilized topical vitamin E with a corticosteroid (Betonil) and found that vitamin E enhanced the therapeutic effect of the corticosteroid [35].…”
Section: In Vivo Human Studiesmentioning
confidence: 99%
“…One study found that the topical application of vitamin E reduced the lesion size, without any therapeutic effects on the clinical symptoms of OLP. Two of three OL studies found that vitamin E applied orally or topically reduced lesion sizes, and histological changes were also observed [33,34]. One SF study utilized topical vitamin E with a corticosteroid (Betonil) and found that vitamin E enhanced the therapeutic effect of the corticosteroid [35].…”
Section: In Vivo Human Studiesmentioning
confidence: 99%